Aerodynamics and Heat Transfer in Polymer Blown Film Processing: Experimental and Numerical Investigation - Zulbakri, Mohammad Luqman; Mat. Rautin, Nur Atiqah; Shuib, Raa Khimi; Ku Ishak, Ku Marsilla; Abdul Hamid, Auratus Zuratul Ain; Shafiq, Mohamad Danial; Idroas, Mohamad Yusof; Abdullah, Muhammad Khalil (Makara Journal of Technology, 2025)
The effects of airflow dynamics, heat transfer, and mechanical properties on the HDPE blown film extrusion process were examined using a single-lip air ring with a fixed compressed-air valve opening angle of 10°. Reynolds numbers ranging from 9175 to 25911 were analyzed to understand their impact on cooling efficiency, bubble morphology, and film properties. Numerical simulations employing the Standard k−ω turbulence model in ANSYS FLUENT v2023, with mesh refinement achieving y+ ≈ 1, captured detailed flow and heat transfer behavior. Results showed that higher Reynolds numbers significantly enhanced the heat transfer coefficient, with values increasing from 1096 W/m²·K at Reynold number of 9175 to 1438 W/m²·K at Reynolds number of 25911, reducing the axial cooling distance by up to 30%. This rapid cooling improved the cooling rate but led to a reduced lay-flat width (from 29.10 cm at a Reynolds number of 9175 to 27.50 cm at a Reynolds number of 25911) and thicker films. The tensile stress decreased from 25.25 MPa at a Reynolds number of 9175 to 20.84 MPa at a Reynolds number of 25911, reflecting the impact of turbulence on the polymer chain alignment. These findings emphasize the trade-offs between enhanced cooling efficiency and material properties, offering critical insights for optimizing blown film extrusion processes for improved quality and operational performance.